Subthalamic nucleus phase-amplitude coupling correlates with motor impairment in Parkinson's disease. - van Wijk, B; Beudel, M; Jha, A; Oswal, A; Foltynie, T; Hariz, M; Limousin, P; Zrinzo, L; Aziz, T; Green, A; Brown, P; Litvak, V (Elsevier, 2016)
Objective High-amplitude beta band oscillations within the subthalamic nucleus are frequently associated with Parkinson’s disease but it is unclear how they might lead to motor impairments. Here we investigate a likely pathological coupling between the phase of beta band oscillations and the amplitude of high-frequency oscillations around 300Hz. Methods We analysed an extensive data set comprising resting-state recordings obtained from deep brain stimulation electrodes in 33 patients before and/or after taking dopaminergic medication. We correlated mean values of spectral power and phase-amplitude coupling with severity of hemibody bradykinesia/rigidity. In addition, we used simultaneously recorded magneto-encephalography to look at functional interactions between the subthalamic nucleus and ipsilateral motor cortex. Results We analysed an extensive data set comprising resting-state recordings obtained from deep brain stimulation electrodes in 33 patients before and/or after taking dopaminergic medication. We correlated mean values of spectral power and phase-amplitude coupling with severity of hemibody bradykinesia/rigidity. In addition, we used simultaneously recorded magneto-encephalography to look at functional interactions between the subthalamic nucleus and ipsilateral motor cortex. Conclusions We speculate that the beta band might impede pro-kinetic high-frequency activity patterns when phase-amplitude coupling is prominent. Furthermore, results provide evidence for a functional subdivision of the beta band into low and high frequencies. Significance Our findings contribute to the interpretation of oscillatory activity within the cortico-basal ganglia circuit.